Analisis Tingkat Kreativitas Siswa Pada Mata Pelajaran Fisika Kelas XII SMAS Ferdy Ferry Kota Jambi - Puspa Cantika Riana (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
Learning creativity is one of the important things in a learning process. The creativity of student in learning will greatly affect the student to obtain a success. This study aims to determine the level of student learning creativity at Jambi City Ferdy Ferry High School on physics subjects. The type of research method used is quantitative research with descriptive analysis. The instrument used was a learning independence questionnaire consisting of 23 statements using 4 likert scales. The subjects of this study were students of class XII Science 3 and XII Science 4 SMAS Ferdy Ferry Jambi City, which totaled 43 student. The results of the questionnaire data were processed using SPPS to get accurate data. The results showed that in class XII Natural Sciences 3 the category was never as much as 9.5% (2 of 21 students), the rare category was 33.3% (7 of 21 students), the frequent category was 38.1% (8 out of 21 students), and the category was always as many as 19% (4 of 21 students). And the results of research from class XII Science 4 categories never amounted to 9.1% (2 of 22 students), rare categories of 18.2% (4 of 22 students), frequent categories of 54.5% (12 out of 22 students), and categories always amounted to 18.2 % (4 out of 22 students). From the research that has been carried out it can be seen that students from both classes are at the same level of creativity.